“I suppose we’ve all been on a bit of a journey”: a qualitative study on providers’ lived experiences with liberalised abortion care in the Republic of Ireland - Brendan Dempsey; Michael Connolly; Mary F. Higgins (Sexual and Reproductive Health Matters)
The aim of this study was to explore service providers’ lived experiences with abortion care in the Republic of Ireland following liberalisation in 2018 via public referendum. Data were collected using semi-structured interviews conducted between February 2020 and March 2021. Thirteen interviews were completed with providers who were directly involved in caring for patients accessing liberalised abortion care in the Republic of Ireland. The sample includes six general practitioners, three midwives, two obstetricians, and two nurses. Interpretative phenomenological analysis identified five super-ordinate themes in the providers’ lived experiences: (1) public reactions to liberalised abortion care; (2) lessons from the service implementation; (3) getting involved in abortion care; (4) moments of moral doubt; and (5) remaining committed to the provision of care. Following liberalisation, providers recalled isolated experiences with anti-abortion sentiments, particularly from those who continue to oppose abortion care. They believed that implementation has been mostly successful in delivering a safe, robust, and accessible service in general practice, though identified ongoing challenges in Irish hospitals. Personally, the providers supported access to care and began providing because they perceived a duty to facilitate access to care. Many, however, reported occasional moral doubts about their work. Despite these, none had considered leaving abortion care and all were proud of their work. They said that patients’ stories were a constant reminder about the importance of safe abortion care. Further work is required to ensure that abortion is fully integrated and normalised and that all providers and patients have access to supports.